Tributação e Direitos Humanos - Renata de Carvalho Salles (Revista Interdisciplinar de Direito, 2010)
We cannot understand the tax without relating it to the rise of state power as a pheno-menon and as an institution structuring of a social order. Indeed, the consolidation of bases stronger state depended - and depends - directly from the use of tax as the primary source of resources to ensure public actions and policies in general. Here, then, that tribute and state are linked structurally and historically.